Optimasi Sodium Starch Glycolate dan Crospovidone sebagai Superdisintegran dalam Sediaan Orally Disintegrating Tablet Meloksikam (Optimization of Sodium Starch Glycolate and Crospovidone as Superdisintegrant in Orally Disintegrating Meloxicam Tablet Dosag - Eunike Aprilianio; Lusia Oktora Ruma Kumala Sari; Eka Deddy Irawan (Pustaka Kesehatan, 2017)
Meloxicam is the second class of biopharmaceutical classification system that its solubility needs to be improved. Therefore, in this study solid dispersion of meloxicam were prepared using PEG 6000. Meloxicam is used to treat osteoarthritis that particularly experienced by geriatric patients. Geriatric patients have a difficulty to swallow conventional capsule or tablet, but orally disintegrating tablet (ODT) overcome this difficulty. The basic of ODT formulation is the use of superdisintegrant, like sodium starch glycolate (SSG) and crospovidone. The aim of this study was to find out the combination of superdisintegrant that shows optimum fomulation. The effect of superdisintegrant and their combination on hardness, friability, disintegration time and percentage of drugs released in 30 minutes (T30) also investigated. The design of formula used the simplex latice design with two component mixture: SSG and crospovidone. Results showed that the combination affected not significantly on disintegration time and friability of ODT, but they could improve hardness and T30. The optimum formula found at combination of 0 mg SSG and 8 mg crospovidone in 200 mg tablet. Keywords: meloxicam, sodium starch glycolate, crospovidone, ODT, simplex lattice design